Variability, Divergence, Heterosis, Combining Ability and Yield Component Studies in Sweet Potatoes (Ipomoea Batatas (L) Lam.) from Sabah and Sarawak, Malaysia - Saad, Mohd Said (1993)
Studies were conducted to examine the breeding potential of the Malaysian indigenous sweet potato germplasm. A total of 99 sweet potato accessions was collected from five different regions in the states of Sabah and Sarawak, Malaysia. A total of 220 polycross progenies was obtained from sixteen randomly chosen accessions planted in a polycross block. The 99 accessions and their 220 progenies were evaluated in the field and 1 6 characters were measured. With the exception of plant type and vine thickness, other characters showed more than 20% CV values. The CV values for yield, tuber number and mean tuber woight were 76%, 57% and 48%, respectively. The means and CV's were similar for all characters between the regions indicating the presence of similar sweet potato type in all the regions. Cluster analysis showed the presence of three main groups of sweet potatoes in the states. Group 1 comprised cultivars with low yield. Cultivars in Group 2 were high yielding with spreading plant type. The third group comprised only six cultivars with orange flesh colour, big leaves, semi-compact plant type and slightly lower yield. The mean, range and CV values for all characters studied were much larger for the polycross progenies as compared to the parents. Cluster analysis showed the presence of seven groups among the progenies indicating the formation of new genotypes as a result of outcrossing. Gene interactions in the new genotypes probably have led to the presence of larger means and ranges of many characters.